Consequences of the COVID-19 Pandemic on Veterinary Anatomy Education in India - Choudhary,Om Prakash (Sociedad Chilena de Anatomía, 2021)
SUMMARY: As the world is struggling to cope with SARS-CoV-2, the aetiological agent of COVID-19, which has led to a global pandemic defying the geographical borders and putting the lives of billions at risk (Priyanka et al., 2020), the most critical question that remains to be elucidated by the faculty of education is whether the virtual mode of teaching will continue or we will be back to the pre-COVID scenario of teaching and learning. Being an assistant professor teaching veterinary anatomy to the students enrolled in the first-year Bachelor of Veterinary Sciences and Animal Husbandry (B.V.Sc. & A.H.), I felt it essential to comment on the impact of COVID-19 pandemic on anatomical education (Franchi, 2020) in India. The present situation of virtual education may impact the future of current veterinary students as practically they can’t be sound just depending on theories.